PREVALENCE OF GENERALIZED ANXIETY DISORDER AMONG MEDICAL STUDENTS: NATIONAL AND INTERNATIONAL STUDIES - Simplicio de Abreu, Josiane; Borges da Silva Bispo, Claudianne (Health and Society, 2025)
Objective: To evaluate the prevalence of generalized anxiety disorder among medical students. Methods: an integrative literature review was conducted. Articles retrieved from the Virtual Health Library (VHL), Latin American and Caribbean Health Sciences Literature (LILACS), Scientific Electronic Library Online (Scielo) and Online System for Search and Analysis of Medical Literature (MEDLINE) were analyzed using the descriptors anxiety, anxiety disorder and medical students. Studies published in Portuguese, English or Spanish and that dealt directly with the subject of study were considered. Results: the prevalence of the analyzed outcome ranged from 19.7% to 50%. The factors associated with the outcome were: female gender, non-heterosexual orientation, feeling very/very afraid of violence in the neighborhood and perceiving access to psychological services as difficult and transition between the basic cycle and the beginning of mandatory internships. Conclusion: the prevalence of the disorder among medical students is significant, which is multifactorial and complex, requiring efforts from educational institutions and public mental health policies aimed at this specific public.